Dysregulated Anxiety and Dysregulating Defenses: Toward an Emotion Regulation Informed Dynamic Psychotherapy - Frederickson, Jon Julius; Messina, Irene; Grecucci, Alessandro (Frontiers in Psychology, 2018)
One of the main objectives of psychotherapy is to address emotion dysregulation that causes pathological symptoms and distress in patients. Following psychodynamic theory, we propose that in humans, the combination of emotions plus conditioned anxiety due to traumatic attachment can lead to dysregulated affects. Likewise, defenses can generate and maintain dysregulated affects (altogether Dysregulated Affective States, DAS). We propose the Experiential-Dynamic Emotion Regulation methodology, a framework to understand emotion dysregulation by integrating scientific evidence coming from the fields of affective neuroscience and Experiential-Dynamic Psychotherapy aimed at resolving DAS. This method and the techniques proposed can be integrated within other approaches. Similarities and differences with the Cognitive model of emotion regulation and cognitive-behavioral approaches are discussed within the paper.